Climate Change Scenarios for the United Kingdom - Technical Report No 1 - Hulme, M; Jenkins, G (1998)
This brochure summarises the content of a report prepared for the UK Climate Impacts Programme (UKCIP) and published by the Climatic Research Unit at the University of East Anglia and the Hadley Centre at the Met. Office. The report describes how the climate of the United Kingdom may change during the next 100 years. In this description, we take into account natural climate variations as well as a range of future greenhouse gas emissions scenarios and different assumed sensitivities of the climate system to these emissions. The resulting climate scenarios are referred to as the UKCIP98 climate scenarios and follow from earlier studies that were published in 1991 and 1996 by the Climate Change Impacts Review Group of the, then, Department of the Environment. These earlier CCIRG91 and CCIRG96 climate scenarios for the UK have been widely used in climate impacts assessments in the UK. The scenarios described here replace these earlier efforts.